CREATION OF MECHANICAL ENGINEERING LABORATORY EQUIPMENT RECORDING APPLICATION USING MICROSOFT ACCESS AT SMK NEGERI 1 PALANGKA RAYA - Satria Wibobo; Vontas Alfenny Nahan; Supriyadi; Debora Debora (Jurusan Pendidikan Teknologi Dan Kejuruan, 2023)
The application for recording laboratory equipment loans has an important role in the efficiency of administration and equipment management in educational environments such as SMK Negeri 1 Palangka Raya. This article describes the development of a Microsoft Access-based mechanical engineering laboratory equipment loan recording application to meet school needs in managing laboratory equipment more efficiently. This application was designed with the unique needs of laboratories in mind, including the process of borrowing and returning equipment, equipment stock management, and reporting on loan activities. Application users, such as laboratory technicians and equipment users, can easily record borrowings, check equipment availability, and generate necessary reports. This application is expected to provide benefits in increasing the efficiency of laboratory administration, increasing the accuracy of recording, and providing convenience in reporting. Apart from that, this application is also expected to increase transparency in the process of borrowing Mechanical Engineering laboratory equipment at SMK Negeri 1 Palangka Raya. The performance evaluation results of this application show that users experience improvements in administrative efficiency, recording accuracy and transparency. Thus, this application makes a positive contribution to the management of the Mechanical Engineering laboratory at SMK Negeri 1 Palangka Raya and can be an example of successful technology implementation in education.